Long-term safety of lumacaftor–ivacaftor in children aged 2–5 years with cystic fibrosis homozygous for the F508del-CFTR mutation: a multicentre, phase 3, open-label, extension study. Issue 9 (September 2021) - Hoppe, Jordana E; Chilvers, Mark; Ratjen, Felix; McNamara, John J; Owen, Caroline A; Tian, Simon; Zahigian, Rachel; Cornell, Alexandra G; McColley, Susanna A
Summary: Background: A previous phase 3 study showed that lumacaftor–ivacaftor was generally safe and well tolerated over 24 weeks of treatment in children aged 2–5 years with cystic fibrosis homozygous for the F508del-CFTR mutation. In this study, we aimed to assess the long-term safety of lumacaftor–ivacaftor in a rollover study of children who participated in this previous phase 3 study. Methods: In this multicentre, phase 3, open-label, extension study (study 116; VX16-809-116), we assessed safety of lumacaftor–ivacaftor in children included in a previous multicentre, phase 3, open-label study (study 115; VX15-809-115). The study was done at 20 cystic fibrosis care centres in the USA and Canada. Children aged 2–5 years with cystic fibrosis homozygous for the F508del-CFTR mutation who completed 24 weeks of lumacaftor–ivacaftor treatment in study 115 received weight-based and age-based doses of oral lumacaftor–ivacaftor: children weighing less than 14 kg and aged younger than 6 years at study 116 screening received lumacaftor 100 mg–ivacaftor 125 mg every 12 h; children weighing 14 kg or more and aged younger than 6 years at screening received lumacaftor 150 mg–ivacaftor 188 mg every 12 h; and children aged 6 years or older received lumacaftor 200 mg–ivacaftor 250 mg every 12 h. Children received treatment for up to 96 weeks, equivalent to up to 120 weeks of treatment in total from the start of study 115 to completion of study 116. The primary endpoint was the safety and tolerability of the study drug in all participants who had received lumacaftor–ivacaftor for 24 weeks in study 115 and had received at least one dose in study 116. Secondary endpoints included change from baseline in study 115 at week 96 of study 116 in sweat chloride concentration, growth parameters, markers of pancreatic function, and lung clearance index (LCI) parameters in all children who received at least one dose of lumacaftor–ivacaftor in study 116. This study is registered with ClinicalTrials.gov, NCT03125395 . Findings: This extension study ran from May 12, 2017, to July 17, 2019. Of 60 participants enrolled and who received lumacaftor–ivacaftor in study 115, 57 (95%) were included in study 116 and continued to receive the study drug. A total of 47 (82%) of 57 participants completed 96 weeks of treatment. Most participants (56 [98%] of 57) had at least one adverse event during study 116, most of which were mild (19 [33%] participants) or moderate (29 [51%] participants) in severity. The most common adverse events were cough (47 [82%] participants), nasal congestion (25 [44%] participants), pyrexia (23 [40%] participants), rhinorrhoea (18 [32%] participants), and vomiting (17 [30%] participants). A total of 15 (26%) participants had at least one serious adverse event; most were consistent with underlying cystic fibrosis or common childhood illnesses. Respiratory adverse events occurred in five (9%) participants, none of which were serious or led to treatment discontinuation. Elevated aminotransferase concentrations, most of which were mild or moderate in severity, occurred in ten (18%) participants. Three (5%) participants discontinued treatment due to adverse events (two due to increased aminotransferase concentrations [one of whom had concurrent pancreatitis], considered as possibly related to study drug; and one due to gastritis and metabolic acidosis, considered unlikely to be related to study drug). No clinically significant abnormalities or changes were seen in electrocardiograms, vital signs, pulse oximetry, ophthalmological examinations, or spirometry assessments. Improvements in secondary endpoints observed in study 115 were generally maintained up to week 96 of study 116, including improvements in sweat chloride concentration (mean absolute change from study 115 baseline at week 96 of study 116 −29·6 mmol/L [95% CI −33·7 to −25·5]), an increase in growth parameters and pancreatic function, and stable lung function relative to baseline, as measured by the LCI. Interpretation: Lumacaftor–ivacaftor was generally safe and well tolerated, and treatment effects were generally maintained for the duration of the extension study. These findings support the use of lumacaftor–ivacaftor for up to 120 weeks in young children with cystic fibrosis aged 2 years and older homozygous for the F508del-CFTR mutation. Funding: Vertex Pharmaceuticals Incorporated.